Analisis Pesan Moral Pada Film The Covenant Karya Guy Ritchie’s - Ferizon, Jordi; Putra, Dilmai; Sari, Sapta (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
A good film should not only function as a medium of entertainment, but also educate its audience and contain various important information about the plot of the film. The film